Challenges and opportunities to a sustainable bioenergy utilization in climate mitigation: a global perspective - Singh, Jagdeep; Clough, Yann (Frontiers in Sustainable Energy Policy, 2024)
Bioenergy is perceived to play a vital role in climate mitigation, transition to renewable energy consumption, energy security, and local and rural socio-economic development. However, exploiting renewable bioenergy resources may need to be more sustainable in the current predominant paradigm. In this study, we raise two broad research questions: (1) what are the significant challenges to the current global bioenergy production and consumption system, and (2) what are the opportunities for a sustainable and circular bioenergy system? We qualitatively analyzed how the current bioenergy production and consumption system results in unintended negative consequences. Taking the example of biofuels, this research exemplifies some critical systemic flaws in how bioenergy is currently utilized in the transportation sector. We do this by broadening the system boundaries to identify the social, economic, and environmental consequences often distant in time and space. We conducted semi-structured interviews, workshops, and literature studies to gather data on the significant bioenergy production and consumption drivers, socio-economic factors, and ecological impacts. The causal loop diagram technique illustrates this broader system's systemic cause-effect and feedback relationships. In the current system of bioenergy production and consumption, negative socio-economic and ecological consequences limit the potential of exploiting bioenergy for climate mitigation. Firstly, bioenergy is neither carbon neutral nor renewable from a broader systems perspective, given that biomass cultivation, feedstock refining, and processing are closely coupled with natural resource use (e.g., water, energy, chemicals, and fertilizers) and other nutrient cycles (e.g., nitrogen, and phosphorus). Secondly, large-scale bioenergy developments negatively impact food security, land use change, ecosystem services, and biodiversity in certain regions. Thirdly, the current globalized bioenergy economy is fundamentally unsustainable due to the displacement of bioenergy production's negative social and ecological impacts from consumer to producer regions. We identify and discuss the critical system interventions to be placed throughout the system as significant leverages for managing the unintended negative consequences of the present dominant bioenergy production and consumption regimes.